ZAKAT FUND DISTRIBUTION MODULE THROUGH COMMUNITY EMPOWERMENT PROGRAMS AT THE NATIONAL BOARD OF ZAKAT IN INDONESIA: A STUDY AT BAZNAS LAMPUNG PROVINCE - Rodliyah, Nunung; Wulandari, Sartika Wulandari; Huda, Sholikhul; Mukaromah, Muhimmatul; Permana Putra, Aldi (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This study scrutinizes structural deficiencies in the governance of productive zakat distribution at BAZNAS Lampung Province, specifically focusing on the absence of empowerment-based distribution modules, mentorship practices that lack clear and measurable competency frameworks, and insufficient long-term monitoring mechanisms. Adopting a normative and empirical approach, the research derives data from in-depth interviews with amil and mustahik, complemented by an analysis of regulatory and institutional documents. Findings indicate that distribution remains predominantly administrative, mentorship lacks measurable competency indicators, and evaluation systems fail to capture sustained trajectories of mustahik business development. The novelty of this research lies in the formulation of an integrated module synthesizing legal perspectives, empowerment theory, and empirical practices to fortify zakat governance. The proposed module encompasses initial assessments, competency-based mentorship, and long-term performance evaluation systems. Theoretically, this study enriches the discourse on zakat governance; practically, it offers a replicable operational model to enhance accountability and mustahik self-reliance.